2006
DOI: 10.1051/0004-6361:20054053
|View full text |Cite
|
Sign up to set email alerts
|

Water ice growth around evolved stars

Abstract: We present combined radiative transfer and H 2 O ice formation calculations for the dusty envelopes of oxygen-rich evolved stars. We study the effects of various (circum-)stellar parameters on the spectral energy distribution of these stars, their infrared spectral water ice features at 3 µm and in the 30−100 µm region, and the properties of (water ice on) the grains in their envelopes. We also study the ice formation process as a function of stellar evolution for a star with an initial mass of 5 M , which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 42 publications
(56 reference statements)
2
26
0
Order By: Relevance
“…Additionally, the ISO spectrum of IRAS 19343+2926 shows the presence of the water ice bands at 62 and 43 μm (Dijkstra et al 2006), confirming the crystalline nature of the water ice in this star. The presence of these latter features cannot be excluded in the case of IRAS 17423−1755 because of the poor quality of the ISO LWS spectrum (see Figure 2).…”
Section: Water Ice In Highly Embedded Evolved Starsmentioning
confidence: 53%
See 4 more Smart Citations
“…Additionally, the ISO spectrum of IRAS 19343+2926 shows the presence of the water ice bands at 62 and 43 μm (Dijkstra et al 2006), confirming the crystalline nature of the water ice in this star. The presence of these latter features cannot be excluded in the case of IRAS 17423−1755 because of the poor quality of the ISO LWS spectrum (see Figure 2).…”
Section: Water Ice In Highly Embedded Evolved Starsmentioning
confidence: 53%
“…Water ice has been observed in a significant sample of AGB stars-in particular in OH/IR stars-some post-AGB stars and a few PN (Omont et al 1990;Eiroa & Hodapp 1989;Hoogzaad et al 2002;Molster et al 2001). The specific conditions for the formation of water ice in circumstellar envelopes around evolved stars have been discussed and modeled by Dijkstra et al (2003Dijkstra et al ( , 2006, who also studied the trends that can be observed in the 3, 43, and 62 μm water ice features during the stellar evolution from the AGB to the PN phase.…”
Section: Water Ice In Highly Embedded Evolved Starsmentioning
confidence: 99%
See 3 more Smart Citations